CML: genetic paradigm of targeted therapy 1 - Deininger, Michael W. (Henry Stewart Talks, 2015)
Typical clinical findings and phases of chronic myeloid leukaemia (CML), Philadelphia chromosome (juxtaposition & genomic anatomy BCR-ABL1), Target cells for transformation, Molecular driver for pathogenesis (BCR-ABL1 tyrosine kinase), Imatinib (inhibitor of BCR-ABL1)